Предмет: Математика, автор: DianOcHka786

2/11(х+у) при х=-13, у=2,

 

-0.8ху при х=-10,у=-0.5

 

-3/4Х(х-у) при х=5,у=13.

 

 

 

(-4/5)Х(-3/8)Х(5/12)

(-9/10)Х5/6Х(-2/3)

 

 

-63Х(7-11)

9.9Х(3-5)

-2.2Х(8-3)

(26-11)Х(-0.4)

(32-40)Х3.5

(0.99-1)Х26

Ответы

Автор ответа: alysik1978
0

  2/11(х+у)=2/11(-13+2)=2/11*(-11)=-2

-0,8ху=-0,8*(-10)*(-0,5)=8*(-0,5)=-4

-3/4*(х-у)=-3/4*(5-13)=-3/4*(-8)=6

 

 

 (-4/5)*(-3/8)*(5/12)=3/10*5/12=1/12

(-9/10)*5/6*(-2/3)=(-3/4)*(-2/3)=1/2

 

 

 -63*(7-11)=-63*(-4)=252

9,9*(3-5)=9,9*(-2)=-19,8

-2,2*(8-3)=-2,2*5=-11

(26-11)*(-0,4)=15*(-0,4)=-6

(32-40)*3,5=-8*3,5=-28

(0,99-1)*26=-0,01*26=-0,26

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

Похожие вопросы
Предмет: Математика, автор: aleksandrovalila05
Предмет: Математика, автор: stitkzkgztks